Entre a Maxambomba e o Bonde de Burros: a chegada de um novo sistema de transporte público no Recife (1867-1889). - Vasconcelos, Lamarck Montenegro de (2021)
The Paradidactic analyze the transformations that occurred in the locomotion of the recifenses with the arrival of the modern public transport equipments in the second half of the XIX century. The local elite, that learned the daily news from the Industrial Europe, was influenced by the modern ideals that bloomed in the bigs urban centers. This urban aristocratic needed to come and go, dry walk, with calm, security and speed, to usual activites, wich gave rise to the Maxambomba appearance, supplying the limitation in the accesses to several places. Residentes, that moved with a primitive form, in precarious roads, demanded the implementation of a transport system that permited the access to the emerging suburbs of the most urban region of Recife, where was concentrate the commerce, the cafes, the theater of Santa Isabel, the shepdherd, the carnaval, the church and the processions. The literate elite observed the City with precarious infrastructure and tried to copy what existed of modern in the mains citys of europe. Although the emergence of the steam train to represent the solution of the sore in the urban transport, in the end of the eight hundred, the population showed unsatisfied with the service quality and the values that was charged for the ticket, announcing the end of the steam train.